Tomato epigenetics: Deciphering the beyond genetic information in a vegetable fleshy-fruited crop - Nogueira, Fabio T. S. [UNESP] (Springer Nature, 2019)
The first natural plant mutant for which the molecular basis was determined to be an epimutation rather than a change in DNA sequence was a peloric variant of toadflax, Linaria vulgaris. Remarkably, the second example of a natural epimutant came from the vegetable fleshy-fruited crop tomato (Solanum lycopersicum). The discovery of the molecular basis for the Colorless nonripening (Cnr) epimutation was a landmark for plant epigenetics and, importantly, linked epigenetic mechanisms with an important agronomical trait. More recently, several studies on tomato have contributed to our better understanding of epigenetic mechanisms underlying important heritable crop traits, such as ripening and stress response. Epigenetic mechanisms have also been associated with transgressive segregation in hybrids generated from crosses between cultivated tomato and close wild relatives. Therefore, we can only envision that tomato will became a model for studying the epigenetic basis of economically important phenotypes, allowing for their more efficient exploitation in plant breeding.